PENGENALAN BAHASA INGGRIS DENGAN STORYTELLING MELALUI FILM ANIMASI ANAK USIA DINI DI TK FADHILAH PADANG - Oktaviani, Lola; Mahyuddin, Nenny (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2019)
Abstract: The purpose of this research is to look at the influence of English vocabulary of children with Story Telling through Animated Films on children's language development in Kindergarten Fadhilah Amal 3 Tunggul Hitam Padang. the activity of introducing English with Story Telling through this Animated Film researchers wanted to see how the deve-lopment of children's language, especially in English at TK Fadhilah Amal 3 Tunggul Hitam Padang. Quantitative research methods used in the form of Quasi Experiments. The population consisted of all 43 Fadhilah Amal 3 Kindergarten students, namely groups B1, B2 and B3. B3 group was used as an experimental sample and B1 as a control class sample of 15 people each. The sampling technique used cluster sampling. The data collection techniques used by teachers' tests, such as statements of 4 statements as well as data collection in the form of statement widths in the form of an instrument lattice. The results of tests conducted using SPSS version 16, with the results obtained in the experimental class obtained an average of 13.13 and a control class 11.60. The conclusion drawn is that there is a significant influence of the activities of introducing English with Story Telling through animated films on children's language skills, especially English, in children in Kindergarten Fadhilah Amal 3 Tunggul Hitam Padang.